The Influence of Leadership Style and Organizational Work Culture on the Performance of Employees of Pucang Sewu Surabaya Health Center - Agus Supriyanto (Lavish Opulent Education, 2025)
This study investigates the influence of leadership style and organizational work culture on employee performance at the Pucang Sewu Public Health Center in Surabaya. As frontline service providers in the public health system, employees at community health centers play a crucial role in delivering quality healthcare. However, preliminary observations revealed indications of underperformance among staff, prompting an exploration of managerial and cultural factors affecting work outcomes. A quantitative research method was employed using a survey distributed to 50 respondents, who are employees of the health center. The collected data were analyzed using multiple linear regression through SPSS software. The study focused on two independent variables—leadership style and organizational work culture—and their respective and combined effects on employee performance. The findings demonstrate that both leadership style and organizational work culture have significant influences on employee performance. Specifically, leadership style was found to have a strong positive effect, while organizational work culture also contributed meaningfully to performance outcomes. The coefficient of determination (R²) was 0.516, indicating that 51.6% of the variance in performance can be explained by the two variables. The remaining 48.4% is likely attributed to other factors not included in the model. The T-test results confirmed the significance of both variables, with leadership style and organizational work culture showing p-values below 0.05. These results validate the hypotheses and underscore the importance of effective leadership and a strong organizational culture in enhancing staff performance in public health institutions. The study contributes to the literature on human resource management in healthcare settings and provides practical insights for managerial improvements at community health centers.